A study on key success factors and variables among cottage and village industries contributing towards consumers satisfaction and loyalty in Northern Kedah / Mohammad Zaki Ayob and Fatimah Mohd Saman - Ayob, Mohammad Zaki; Saman, Fatimah Mohd (2018)
Numerous efforts had been undertaken by government agencies to improve rural poverty . One initiative is establishing cottage-based enterprises that are intended to function as all-year revenue generato rs for farm families. The issues related to this initiative are market acceptance, competitive advantage, customer satisfaction, and loyalty toward these products . This study was thus conducted to find out present customer ratings on important variables that contribute to customer satisfaction and loyalty. A group of existing and potential customers were selected to provide feedback for this study and their age group range from 13 to 25 years old. However, 73.7% of the selected respondents were above 20 years. Sample subjects were subsequently interviewed based on some '· ~as te tests" provided and data were collected after the taste test. Due to the lack of a reliable sampling frame, nonprobability sampling technique was used. The selection of sample subjects was based on their ability to discriminate product attributes and assess service quality. The information collected relates to Product Quality (taste, packaging, freshness, attractiveness, and health benefits), Service Quality (availability, price, display, and promotion), Customer Satisfaction (value for money , fulfillment , overall quality, and exceeding expectations), and their indication of Product Loyalty (comparable to ideal, willing to recommend, confident people will be loyal , self willing to be loyal) . The period of study was from September 2004 to April 2005. The Structural Equations Modeling was utilized to obtain an acceptable model , regression coefficients and causal strengths oflatent (y) and measured (A) variables. The., tes t result shows that presently Service Quality influences 71.3% towards Customer Satisfaction while Product Quality only influences 14.7%. Customer Satisfaction, however, explains 98% of Customer Loyalty. Based on these data, the current predictor of Customer Satisfaction is Service Quality. Hence , there is a need to enhance Product Quality and its attributes besides maintaining Service Quality .